Teaching English for Young Learners (TEYL) in Indonesia: Policies, Implementations, and Future Directions - Rahman, Fadhlur; Asirah, Asirah; Saputra, Nizar; Safitri , Rizka; Muntasir, Muntasir (Seulanga : Jurnal Pendidikan Anak, 2025)
The teaching of English For Young Learners (TEYL) in Indonesia has become increasingly prominent in response to globalization and the growing need for English proficiency in academic and professional spheres. Despite this rising demand, the implementation of English education at the early childhood and primary school level encounters significant challenges. These include inconsistent educational policies, a lack of adequately trained teachers, and insufficient teaching and learning resources. This study investigates the current landscape of English language education for young learners in Indonesia by examining national education policies and classroom practices. The research identifies key issues such as the incongruent of a standardized curriculum, minimal pre-service and in-service teacher training specific to TEYL, and disparities in access to quality English instructions and materials between urban and rural schools. Therefore, this current study proposes a strategic roadmap aimed at enhancing the quality and effectiveness of TEYL in Indonesia. These include policy reforms, targeted teacher development programs, curriculum enhancements, and improved resource allocation. The findings are intended to inform policymakers, educational institutions, and practitioners in developing a sustainable roadmap for TEYL in Indonesia.